The Positive School Culture Management and Student Wellbeing - I Eskasasnanda (Studies in Learning and Teaching, 2026)
Education is an important asset to build intelligent and civilized people for the future of a nation. One obstacle that hinders effective education in Indonesia is that schools have not optimally considered the importance of well-being for the success of student education. This study is a qualitative organizational ethnography study that examines how state junior high school organizations try to create student well-being. Data and information collection was carried out with three main activities: observation of student learning activities in class and school, interviews with principals, teachers, and students, and school document studies. The results of this study indicate that the school's ability to communicate and establish partnerships with parents is the main key to building student well-being. Schools that have strong partnerships with parents can make students prosperous because they can develop and grow optimally, have a sense of autonomy; have good social relations with teachers and peers; and get satisfactory recognition from parents as the closest and most important people to them.